Antibiotic resistance and virulence factors among escherichia coli isolates from avian organic fertilizer - Agostinho, Juliana Maria Avanci [UNESP]; Cardozo, Marita Vedovelli [UNESP]; Borzi, Mariana Monezi [UNESP]; Marin, José Moacir (FapUNIFESP (SciELO), 2020)
Brazilian poultry industry generates large amounts of organic waste, such as chicken litter, which is often used in agriculture. Among the bacteria present in organic fertilizer are members of the Enterobacteriaceae family, such as Escherichia coli. The aim of this study was to analyze the profile of virulence factors and antimicrobial resistance of E. coli isolates from avian organic fertilizer. A total of 47 E. coli strains were tested through Polymerase chain reaction to detect virulence genes (hlyF, iss, ompT, iutA and iroN). Fourteen antimicrobials were used to test antimicrobial susceptibility in the strains. Genes characteristic of Avian Pathogenic E. coli (APEC) were reported among the strains, with the hlyF, iss and ompT genes being the most prevalent. The isolates showed high resistance (˃50%) to tetracycline, gentamicin, cefotaxime, nitrofurantoin, trimethoprim-sulfamethoxazole and ampicillin. Multidrug resistance was reported in a great number of strains (>70%). The results showed the presence of APEC cells with virulence genes and antimicrobial resistance after 15 days of the windrowing process in poultry houses, it means this process should be improved to eliminate these cells.
Resistência a antibióticos e fatores de virulência entre isolados de escherichia coli provenientes de fertilizante orgânico aviário
Keywords: Enterobacteriacea; Poultry production; Virulence factors; Zoonotic risk